Covid to beat: creative intermingling of translingualism in comic if Malaysia was anime: Covidball Z - Wirda Syaheera Sulaiman; Shin, Yi Chew (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia, home to a multiracial community consisting of Malay, Chinese, Indian and others, typically practise two or more languages as Malay language is the official national language and English is the second language. The use of translanguaging amongst Malaysians is regular in spoken as well as written discourse. This particular research examined the use of translanguaging in written discourse, specifically in a comic book by Malaysian cartoonist Ernest Ng titled If Malaysia was Anime: Covidball Z. This comic book addresses real Malaysian scenarios such as the recent Covid-19 pandemic and political scenes with an adoption of Malaysian style of spoken discourse in written form. This research aims to explore the use of translanguaging in the mentioned comic book and explore Malaysians’ views of the use of translanguaging in this comic book through interviews. To determine the use of translanguaging in the comic book, this study adopted Jakobson’s (1987) six language functions as the theoretical framework. The findings of this study revealed that out of the six language functions stated by Jakobson, five were found in the comic book excluding the phatic function. Most interviewees were also found to have positive perceptions towards the use of translanguaging in comic books as it could display Malaysians’ unique plurilingual communication skills.